The Effect Of Baby Massage With Orange Therapy On The Sleep Needs Of 6-12 Months In Baby Clini c, Rismala Kisaran, Asahan Regency - Mahyunidar Mahyunidar; Juliana Juliana (Institute of Computer Science (IOCS), 2022)
Sleep disturbances in infants are a form of problems faced by parents. Based on WHO data in 2012 in the journal Pediatrics, as many as 33% of infants experienced sleep disorders (Abdurrahman, 2015). According to the results of Sekartini's research, which was conducted in 5 cities, namely Jakarta, Bandung, Medan, Palembang and Batam with a total of 385 respondents, data was obtained that 51.3% of infants had sleep disturbances, 42% had less than 9 hours of sleep at night, and woke up at night. more than three times and long waking at night more than one hour (Nurella, 2017). In the Yogyakarta area in 2018, 13.6% of babies who were not routinely given massage therapy experienced problems in their sleep (Fauziah & Wijayanti, 2018). This research was conducted at the Rismala Midwife Clinic. This study aims to determine the effect of baby massage with the aroma of orange terpai on the fulfillment of sleeping needs for babies 6-12 months. The design of this study was a quasi-experimental with a sample size of 31 using one group pre post test without control. The sampling technique is by accidental sampling. Data analysis used paired T test. The statistical test shows that the Sig value is 0.014 <0.05, then H0 is rejected and Ha is accepted.